All Days 2016
DOI: 10.4043/27333-ms
|View full text |Cite
|
Sign up to set email alerts
|

Pack Ice Loads on Seasonally Operating Semi-Submersible in the Labrador Sea

Abstract: Semi-submersible drilling platforms are typically moved off site given any threat of pack ice incursion. Operations in icy waters requires considerations of, amongst others, ice interations with the facility. The offshore industry will benefit from a standardized methodology to evaluate the capability of semi-submersibles in ice during drilling operations. Operators and drilling contractors are particularly interested in understanding how the drilling season may be extended into the shoulder season. This requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The values were selected by considering the capabilities of the testing apparatus, i.e., its power output. Experiments showed that the indentation depth in the studied range had no significant effect on the measured reaction forces [8]. While most of the indenter's surface is constantly in contact with the ice, the pressure on the surface varies.…”
Section: Related Workmentioning
confidence: 89%
See 4 more Smart Citations
“…The values were selected by considering the capabilities of the testing apparatus, i.e., its power output. Experiments showed that the indentation depth in the studied range had no significant effect on the measured reaction forces [8]. While most of the indenter's surface is constantly in contact with the ice, the pressure on the surface varies.…”
Section: Related Workmentioning
confidence: 89%
“…Finally, different studies use different values for the failure stress parameters, and such discrepancies are due to the differences in geometries, types of experimentally obtained data, and calibration approaches. In a recent series of experiments, medium-scale indentation tests were conducted with rigid indenter and laboratory-grown samples of freshwater ice [8]. The diameter of the indenter is 32.4 cm, which is intended to mimic a pipeline.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations